(untitled) (Journal of Engineering, 2024)
One of the challenges that developing countries is the necessity to properly manage the risks involved in road construction projects. For that, the present work developed a dissension method to specify effective risk factors in a wide range of approaches and protocols to achieve its objectives. The Influence of Risk Road Implementation on Performance Indicators The initial sets of outcomes were derived from computing the average risk estimate. Subsequently, the second results group was established by assessing the relative importance index (RII) effects. In the RII method and mean results the workers and machinery insurance is the most important. The identical data that had been collected from the weighted product model (WPM) methodology ultimately determined that the essential resources such as staff and equipment must be accessible through all stages of activity. In road construction, machines represent a major effective factor that can help to project success with a rank of 0.868. Also, the worker conditions and skills represent another strategy in projects with 0.547 rank. The weighted product model results yelled a more accurate and practical output.